Madwomen : the "Locas mujeres" Poems of Gabriela Mistral, a Bilingual Edition. - Mistral, Gabriela (University of Chicago Press, 2008)
A schoolteacher whose poetry catapulted her to early fame in her native Chile and an international diplomat whose boundary-defying sexuality still challenges scholars, Gabriela Mistral (18891957) is one of the most important and enigmatic figures in Latin American literature of the last century. The Locas mujeres poems collected here are among Mistral's most complex and compelling, exploring facets of the self in extremispoems marked by the wound of blazing catastrophe and its aftermath of mourning. From disquieting humor to balladlike lyricism to folkloric wisdom, these pieces enact a tragi.